The Mitochondrion as an Emerging Therapeutic Target in Cancer. Issue 1 (January 2020) - Roth, Katherine G.; Mambetsariev, Isa; Kulkarni, Prakash; Salgia, Ravi
Abstract : Mitochondria have emerged as important pharmacological targets because of their key role in cellular proliferation and death. In tumor tissues, mitochondria can switch metabolic phenotypes to meet the challenges of high energy demand and macromolecular synthesis. Furthermore, mitochondria can engage in crosstalk with the tumor microenvironment, and signals from cancer-associated fibroblasts can impinge on mitochondria. Cancer cells can also acquire a hybrid phenotype in which both glycolysis and oxidative phosphorylation (OXPHOS) can be utilized. This hybrid phenotype can facilitate metabolic plasticity of cancer cells more specifically in metastasis and therapy-resistance. In light of the metabolic heterogeneity and plasticity of cancer cells that had until recently remained unappreciated, strategies targeting cancer metabolic dependency appear to be promising in the development of novel and effective cancer therapeutics. Highlights: Mitochondria display a dynamic and heterogeneous phenotype that facilitates the metabolic heterogeneity and plasticity of cancer cells. The altered metabolic functions and dynamics of mitochondria in cancer cells, as well as mitochondrial evasion of apoptosis, provide targets for novel cancer therapeutics. The mitochondrial network has distinct morphological features that appear to be interrelated with mitochondrial dynamics. Fractal measurements to evaluate the mitochondrial network alongside the metabolic profile of tumors may provide insight into tumor sensitivity to mitochondrial therapeutics. Although there are a few FDA-approved cancer-directed therapies that specifically target mitochondria, numerous therapies have been evaluated in clinical trials that target mitochondrial metabolism and evasion of apoptosis, with promising results in a variety of cancer types.